Identification and quantitation of vesivirus 2117 particles in bioreactor fluids from infected Chinese hamster ovary cell cultures1. Issue 5 (25th December 2012) - Qiu, Yongchang; Jones, Nathan; Busch, Michelle; Pan, Peng; Keegan, Jesse; Zhou, Weichang; Plavsic, Mark; Hayes, Michael; McPherson, John M.; Edmunds, Tim; Zhang, Kate; Mattaliano, Robert J.
Abstract The prevention of adventitious agent contamination is a top priority throughout the entire biopharmaceutical production process. For example, although viral contamination of cell banks or cell cultures is rare, it can result in serious consequences (e.g., shutdown and decontamination of manufacturing facilities). To ensure virus free production, numerous in vivo and in vitro adventitious agent assays and biophysical characterizations such as electron microscopy are conducted on cell banks, raw materials, process materials, and drug substances throughout the manufacturing process. Molecular assays such as PCR and other nucleotide‐based techniques are also routinely used for screening and identification of any viral agents. However, modern techniques in protein identification of complex protein mixtures have not yet been effectively integrated throughout the industry into current viral testing strategies. Here, we report the identification and quantitation of Vesivirus 2117 particles in bioreactor fluid from infected Chinese hamster ovary cell cultures by global protein sequencing using mass spectrometry in combination with multi‐dimensional liquid‐chromatography. Following mass spectrometric data acquisition and rigorous data analysis, six virus specific peptides were identified. These peptides were fragments of two structural proteins, capsid protein pre‐cursor (four unique peptides) and small structural protein (two unique peptides), from the same species: Vesivirus 2117. Using stable heavy isotope‐labeled peptides as internal standards, we also determined the absolute concentration of Vesivirus particles in the bioreactor fluid and the ratio of two capsid proteins (VP1:VP2) in the particles as approximately 9:1. The positive identification of Vesivirus 2117 was subsequently confirmed by RT‐PCR. Biotechnol. Bioeng. 2013; 110: 1342–1353. © 2012 Wiley Periodicals, Inc.